MODEL PEMBELAJARAN INKUIRI TERBIMBING BERWAWASAN PENDIDIKAN KARAKTER UNTUK MENINGKATKAN HASIL BELAJAR SISWA SMP - Maria Agatha Hertiavi (Program Studi Pendidikan Biologi FKIP Unpatti, 2017)
Background: Survey of researchers in SMP N 38 Semarang, it turns out there are still many teachers who use conventional learning methods and combinations of several methods have not involved students' cognitive, affective, and psychomotor aspects. Learning activities are still dominated by teachers. This resulted in students tend to be passive and the classroom atmosphere became teacher centered. To overcome this problem learning needs to be varied so that the learning process activates students more. Method: The study was conducted through the development method (research and development) which consisted of three stages, namely introduction, development, and evaluation. Results: Based on data analysis, cognitive learning outcomes reached 71.4% completeness with the results of the Gain Test of 0.71 (high gain category). Psychomotor learning outcomes achieved 74.60% achievement, achievement of affective learning outcomes was 73.39% while inquiry skills gained 71.52%. Conclusion: Based on the achievement of learning outcomes, it can be concluded that the devices developed are considered effective. Positive responses of students to teaching materials were 86.40%, while the positive responses of students to LKS reached 87.46%. This means that learning devices developed can be applied in learning.